STEM-Integrated Phyphox to Enhance Student Engagement and Understanding of Newton’s Law - Priscilia, Masayu Putri; Haryani, Fairusy Fitria; Astuti, Linda Dwi; Ramli, Murni; Indriyanti, Nurma Yunita; Sarwendah, Sarwendah; Novia (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2025)
The COVID-19 pandemic has significantly impacted educational technology, such as virtual labs, simulations, and various learning software, to facilitate physics experiments. In the post-pandemic era, virtual laboratory continues to be used in hybrid and face-to-face learning. However, virtual laboratories lack the practical skills of students compared to hands-on experiments. Phyphox (Physical Phone Experiment), an open-source tool that utilises mobile device sensors, addresses the problem by integrating students’ practical skills. This study examines the integration of Phyphox in STEM-based physics learning, with a focus on Newton's Laws. Using an exploratory sequential mixed methods approach, the research examines how Phyphox can enhance student engagement and understanding of complex physics concepts. The first phase involves designing and implementing experiments related to Newton's Laws using Phyphox, while the second phase tests the application in authentic learning contexts. The study employs pretests, post-tests, and questionnaires to evaluate the effectiveness of this approach. Results indicate that STEM-based learning integrated with Phyphox significantly improves student learning outcomes and engagement. Students reported positive experiences, highlighting the app's ease of use, accurate data, and ability to make learning more interactive and enjoyable. The research sample consists of two experimental classes from grades XI Senior High School 1 Karanganyar, with 33 students per class, selected via a Cluster Random Sampling method from the school's overall population. The findings suggest that integrating Phyphox into physics learning can provide valuable guidance for teachers, students, and researchers to develop more effective and engaging STEM education methodologies.